2021
DOI: 10.1128/jvi.00596-21
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide CRISPR Screen Identifies RACK1 as a Critical Host Factor for Flavivirus Replication

Abstract: Cellular factors have important roles in all facets of the flavivirus replication cycle. Deciphering viral-host protein interactions is essential for understanding the flavivirus lifecycle as well as development of effective antiviral strategies. To uncover novel host factors that are co-opted by multiple flaviviruses, a CRISPR/Cas9 genome wide knockout (KO) screen was employed to identify genes required for replication of Zika virus (ZIKV). Receptor for Activated Protein C Kinase 1 (RACK1) was identified as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Our study provided an unprecedented mapping of the DENV RC host interactome and identified cellular modules exploited by DENV during active replication. By combining these proteomics data with gene silencing experiments, we identified a set of Host Dependency Factors (HDFs) that critically impact DENV infection and established an important role for Receptor for Activated C-Kinase 1 (RACK1) in DENV vRNA amplification 12 , which was recently confirmed by others 13 .…”
Section: Introductionmentioning
confidence: 69%
“…Our study provided an unprecedented mapping of the DENV RC host interactome and identified cellular modules exploited by DENV during active replication. By combining these proteomics data with gene silencing experiments, we identified a set of Host Dependency Factors (HDFs) that critically impact DENV infection and established an important role for Receptor for Activated C-Kinase 1 (RACK1) in DENV vRNA amplification 12 , which was recently confirmed by others 13 .…”
Section: Introductionmentioning
confidence: 69%
“…The Receptor for Activated C Kinase 1 (RACK1) protein is a known scaffolding protein with roles in protein shuttling, anchoring, and stabilization, as well as mediating cellular pathways through protein interactions ( Adams et al, 2011 ). The interaction between DENV NS1 and host RACK1 was first identified in a DENV NS1 specific proteomics screen ( Hafirassou et al, 2017 ) but the role of this interaction was not fully explored until recently by Shue et al (2021) . They performed a genome-wide CRISPR knockout screen in Huh7 cells to identify host genes involved in ZIKV replication.…”
Section: Er Remodeling and Virus Replication Compartment Formationmentioning
confidence: 99%
“…Using a Renilla luciferase DENV replicon they determined that RACK1 specifically played a role in viral genome replication, rather than viral entry or translation. Using replication-independent expression system that induces the formation of replication compartments in the ER without virus infection they found that RACK1 silencing led to reduced formation of these compartments in the ER ( Shue et al, 2021 ). These studies are a great example of the power of integrating proteomic and genetic screens to identify mechanisms of virus replication.…”
Section: Er Remodeling and Virus Replication Compartment Formationmentioning
confidence: 99%
“…In addition, recent CRISPR KO screens have been published including a genome-wide screen with ZIKV performed in human stem cells differentiated into neural progenitor cells [ 37 ], a ZIKV screen in Huh-7.5 cells [ 38 • ], and screens with ZIKV and YFV in HAP1 cells [ 21 • ]. Highlights from these reports include mechanistic follow-up where Shue et al show that RACK1 is required for multiple mosquito-borne and tick-borne flaviviruses as well as the coronavirus, SARS-CoV-2 [ 38 • ]. The results indicate that RACK1 may be involved in establishing ROs on the ER membrane.…”
Section: Low-biased Approaches To Identify Flavivirus Host Factorsmentioning
confidence: 99%